Activity Of Lingzhi Fungan Ethanol Extract (Ganoderma Lucidum) Using Soxhlet Method For Bacteria Propionibacterium Acnes - Handrianto, Prasetyo (Universitas Islam Lamongan, 2020)
The purpose of this study is to know Lingzhi Mushroom extract (Ganoderma Lucidum) has antimicrobial activity against Propionibacterium acnes using Ethanol Solvent, the method used is the disc diffusion method using 6 repetitions, the concentration used is 20 µg / ml, 40 µg / ml, 60 µg / ml / ml, 80 µg / ml and 100 µg / ml, Lingzhi mushroom was extracted using ethanol solvent with the Soxhlet method. The results of the research data showed that the largest inhibitory zone was shown at a concentration of 100 µg / ml of 6.91 mm with a medium inhibitory category. The conclusion of this research is the Lingzhi mushroom is able to inhibit the activity of Propionibacterium acnes in the medium category.